One size fits all? Sensitivity to moment of inertia information from tennis rackets in children and adults - Beak, S.; Davids, K.; Bennett, S. (2001)
Work in ecological psychology has shown that younger and older adults are able to perceive key characteristics of wielded rackets through haptic information related to touch and feel. Our study examined the non-visual perception of moment of inertia information by children and adults when wielding tennis rackets. Three groups (children; inexperienced and experienced adult tennis players; n=10 in each) were required to choose, through wielding, three preferred rackets from six available for striking a ball to a maximum distance. Participants in our study selected rackets under two separate conditions differing only in availability of visual information. Choices of racket were each given a weighted score and subjected to a statistical analysis (2 x 3 (condition by group) ANOVA with repeated measures on condition).